Effects of context and relative rank on mate choice and affiliation ratings - Honey, P. Lynne (My University, 2009)
Female dominance has not often been studied as a factor in mate choice and other social interactions. When it has been examined, there have been a number of conflicting findings. The present study was designed to clarify interpretations of a study conducted by Brown and Lewis (2004) that found that men prefer subordinate women in a workplace context. We presented participants with information about the relative rank of physically attractive targets, in two very different contexts (work-related and recreational). We found that the context in which rank cues are presented has an impact on affiliation ratings, but that cues of rank do not affect mate choice ratings. Future studies of effects of dominance must take into account the context in which they are presented, and recognize that rank may not be a sufficient indicator of dominance for the purpose of mate choice by both men and women.
Keywords: dominance; mate choice; attraction; sex differences